2007
DOI: 10.1159/000102534
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1-Induced Pulmonary Vasoreactivity Is Regulated by ET<sub>A</sub> and ET<sub>B</sub> Receptor Interactions

Abstract: Background: Roles of endothelin (ET) receptors (R) and of the endothelium on ET-1-induced pulmonary vasoreactivity are subjects of debate. This stems from endothelial ETB-R that can release both vasodilators and vasoconstrictors. The aim of this study was to evaluate the roles of the endothelium and of ET-Rs on ET-1-induced pulmonary vasoreactivity. Methods: Pharmacological experiments were performed in isolated rat lungs and in pulmonary resistance arteries. Results: In isolated lungs, ET-1 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
2
50
0
2
Order By: Relevance
“…Previous investigators such as Mickley [29] and Adner [30] have previously reported the existence of an interaction between the two receptor subtypes in small mesenteric arteries. We have also recently demonstrated the existence of an interaction between the ET A and ET B receptor to induce the ET-1 vasoconstriction in pulmonary resistance arteries [17]. Whether this inter-play occurs post-receptor or takes place at the receptor level, remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous investigators such as Mickley [29] and Adner [30] have previously reported the existence of an interaction between the two receptor subtypes in small mesenteric arteries. We have also recently demonstrated the existence of an interaction between the ET A and ET B receptor to induce the ET-1 vasoconstriction in pulmonary resistance arteries [17]. Whether this inter-play occurs post-receptor or takes place at the receptor level, remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
“…In pulmonary arteries isolated from sham animals, selective ET A , selective ET B and dual ET A/B (bosentan) receptor antagonists had no significant effect on ET-1-induced response. We have previously demonstrated that at these concentrations, the selective ET A and ET B receptor antagonists had little effect on ET-1-dependent response [17]. It is difficult, however, to reconcile the lack of effect of the dual antagonist bosentan as this antagonist simultaneously blocks both receptors (ET A /ET B ) responsible for ET-1-induced pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other than the serotonin system, endothelin-1/endothelin-1 receptors also play an important role in the development of PAH. 50 Bosentan, a dual antagonist for endothelin-1 receptors, is clinically used for PAH. In animal models, bosentan attenuated vascular remodeling or hypertrophy or both.…”
Section: -Ht2brmentioning
confidence: 99%